Meta-analysis Number of Plants Drugs Used by Characteristics Socioeconomic Factors, Environmental and Geographic - Febiola Diah Pratiwi; Ervizal A. M. Zuhud; Yeni Herdiyeni (Media Konservasi, 2017)
Ethnobotany is the study of public relations with the use of plants. Use of plants by people influenced by several factors, such as social, cultural, socioeconomic, and geographic. Most of the ethnicities in Indonesia has a high dependence on plants medicine for survival. However, the factors that influence the use of medicinal plants by people in Indonesia have not been studied, so that research is needed to optimize the use of medicinal plants to sustainability benefits. The purpose of this study is to analyze the number of species of plants medicine used by the influence of socio-economic, environmental, and geographic factors using principal component analysis and analyzing patterns of use of plants medicine. The results showed that the economy and infrastructure components (access to electricity, means of education, income level, health facilities, distance from the highway, remoteness, and the fastest time toward the road) and the number of people graduating from elementary school affect the number of medicinal plant species used. Based on the results of the study of literature and field observations, the pattern of use of plants medicine in addition to be used as medicine, the plant is used for food, building materials, plant ornamental, ceremonial, wood, wicker and crafts, coloring agents, animal feed, ingredients aromatic, and pesticide. The usage patterns in each region or village has the distinction of which is influenced by the remoteness factor due to the differences in the social, economic, environmental, and geographic.  Keywords: ethnobotany, plants medicine, principal component analysis